FILOSOFI PENDIDIKAN KATOLIK DALAM PERSPEKTIF FILSAFAT ARISTOTELIAN - Agustinus Wisnu Dewantara (Lembaga Penelitian STKIP Widya Yuwana, 2019)
The progress of human civilization today is inseparable from the role of science. The dynamics of the pattern of our daily lives from time to time it runs in line with the dynamics of the development of science. The development of science and human civilization running together since from classical times, the middle ages, modern times, and so on. Novelty found in a period becomes an essential ingredient for other discoveries in the next period. One thing that is difficult to argue is that almost all sides of human life today has been entered by the various effects of the development of science and technology, ranging from economic, political, social and cultural, communication, education, health, and so on. All this progress is the fruit of the development of science that never recede from human studies. This paper on the one hand want to observe the philosophical basis for the world of Catholic education, and on the other hand, this article seeks to contribute a little reflection, especially for teachers of religious education in STKIP Widya Yuwana and Catholic families today. There wilderness philosophy that is so tempting to dive, but the limitations of time and space makes this paper should choose to focus. Perspective selected is Aristotelian philosophy.